Islamic social finance in Indonesia: Opportunities, challenges, and its role in empowering society - Hendri Hermawan Adinugraha; Muhammad Shulhoni; Dliya’udin Achmad (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This study identifies and analyzes Islamic social finance's potential, opportunities, challenges, roles, and impacts in empowering people in Indonesia.Methodology – This research used descriptive and explorative qualitative methods with a systematic literature review. This study used data analysis techniques and content analysis. Findings – This research shows enormous potential for Islamic social finance in Indonesia. Indonesia’s opportunity as a country that has the largest Muslim population in the world and has a large market potential for Islamic social finance. Challenges in developing Islamic social finance, namely the low support for Islamic social finance, the absence of Islamic banks that have maximum assets, the lack of qualified Islamic economic, human resources in the field of Islamic social finance, and the low capacity of research and development of Islamic social finance. Islamic social finance is oriented toward social welfare. This is concrete evidence of its strategic role in community empowerment and poverty alleviation in Indonesia. Islamic social finance is proven to be the main instrument that has a central role in sustainable poverty alleviation that impacts the benefit of all society. Implications – Islamic social finance should integrate with other Islamic philanthropic institutions domestically and globally to expand its impact in empowering people in Indonesia.Originality – This highly structured and in-depth literature review examines and describes the potential, opportunities, challenges, roles, and impacts of Islamic social finance.